Analysis of Social and Emotional Loneliness According to Glasser's Basic Needs - Mustafa Kutlu; Mustafa Pamuk (ÜNİVERSİTEPARK Limited, 2016)
The purpose of this study is to examine the social and emotional loneliness of university students based on the five basic needs set by Glasser. The Social and Emotional Loneliness Scale and University Students Basic Needs Scale were used in this study. A total of 371 students, 206 (55.5%) female and 165 (44.5%) male, who were studying in the Faculty of Education, participated in the study. Correlation, kurtosis, skewness values, Cronbach Alpha internal consistency coefficients, t-test, simple and multiple regression analyses were conducted throughout the study. According to the study findings, social and emotional loneliness does not differ according to gender. It was observed that survival, power, freedom, and fun, which are among the basic needs, do not predict social and emotional loneliness. Only love and belonging were observed to predict both social and emotional loneliness.